Implikatur Percakapan dalam Pidato Donald Trump di Sidang PBB ke-80 - Salwaa Hanifah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Language plays an important role in human communication, including international political communication. In pragmatics, the meaning of an utterance is understood not only explicitly but also through implied meanings known as conversational implicatures. This study aims to analyze the conversational implicatures and their meanings found in Donald Trump’s speech at the 80th United Nations General Assembly. This research employed a qualitative approach with a descriptive method. The data consisted of utterances containing conversational implicatures taken from Donald Trump’s speech published on the official UN Web TV platform. The data were collected through observation and note-taking techniques. The results of the study show that Donald Trump’s speech contains various conversational implicatures in the form of satire, criticism, sarcastic humor, political emphasis, and self-image building. These implicatures were used to convey meanings indirectly in order to influence the audience’s perspective and strengthen his political position in the international community. Therefore, the use of conversational implicatures in political speeches plays an important role as a communication strategy to implicitly convey ideology, criticism, and the speaker’s self-image.